An Unfinished Council : Vatican II, Pope Francis, and the Renewal of Catholicism - Gaillardetz, Richard R., 1958- (Book collections on Project MUSE., 2015)
The Second Vatican Council has become an indespensable referencce point for understanding Roman Catholicism today. Yet in spite of its impact, Vatican Ii was in many ways an unfinished council. The council bishops were able to establish key pillars in the construction of a new vision for the church of our time, but, for various reasons, they were not able to draw those pillars together into a coherent, unified structure. This volume describes both the council's building project itself and the challenges facing the church today if we are to complete the project begun fifty years ago.